1969
DOI: 10.1115/1.3591505
|View full text |Cite
|
Sign up to set email alerts
|

Noise of Involute Helical Gears

Abstract: The problem of involute helical gear noise is studied by running a pair of 6 DP gears in a power circulating rig inside an anechoic room. More than 3500 magnetic tape recordings were taken and analyzed, for gears running at different speeds and transmitting different loads. A pair of 14 DP nickel steel gears of finished, ground, and shaved teeth was also tested to study the effect of surface finish on gear noise. Experimental results revealed that the main sources of gear noise are impact between gear teeth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to that, as long the common tooth width is imposed to be an integer multiple of the axial pitch (px), the sum of the lengths of the components (contacting generating lines) remains constant and thus torsional excitation can be avoided. This is in fact true, but subsequent research [12,13] has shown that this cannot be substantiated, since the common tooth width must be determined from different consideration, because other types of excitations are also present. Subsequent research [7,8,11] confirmed this hypothesis that significant results in reducing vibration excitation can be achieved by expedient modification of the contact zone.…”
Section: The Effect Of the Changed Contact Zone On The Length Of The Contacting Generating Linesmentioning
confidence: 99%
“…According to that, as long the common tooth width is imposed to be an integer multiple of the axial pitch (px), the sum of the lengths of the components (contacting generating lines) remains constant and thus torsional excitation can be avoided. This is in fact true, but subsequent research [12,13] has shown that this cannot be substantiated, since the common tooth width must be determined from different consideration, because other types of excitations are also present. Subsequent research [7,8,11] confirmed this hypothesis that significant results in reducing vibration excitation can be achieved by expedient modification of the contact zone.…”
Section: The Effect Of the Changed Contact Zone On The Length Of The Contacting Generating Linesmentioning
confidence: 99%
“…The finite element/boundary element method (FEM/ BEM) is the prevailing method applied to the numerical analysis for the gearbox vibration and noise. [1][2][3] Kubur et al 4 proposed a dynamic model of a multi-shaft helical gear reduction unit formed by N flexible shafts, and studied the influence of bearing stiffness, shaft size, and other parameters on the vibration of the gearbox. Later, Wei et al 5 established the coupled nonlinear dynamics model of a wind turbine planetary gear transmission system, and proposed a lightweight and reliability constrained optimization design method according to the sequential quadratic programming algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In the early research on gear noise, many empirical formulas for estimating noise intensity were obtained through experiments. [16][17][18] However, the shape of the housing is one of the main factors in the radiated noise of the gearbox, so these empirical formulas may not be suitable for other gearboxes because the radiated noise is strongly dependent on the shape of the housing. Subsequently, the vibration and noise of gearbox is mainly studied by numerical simulation, among which the finite element method/boundary element method (FEM/BEM) is the most widely used.…”
Section: Introductionmentioning
confidence: 99%